Effect of ultra‐high pressure and ultra‐high temperature treatments on the quality of watermelon juice during storage. Issue 9 (12th August 2021) - Liu, Qing; Huang, Guangxue; Ma, Changlu; Li, Guangyan; Wang, Rufu
Abstract: The watermelon juice was treated with ultra‐high pressure (UHP, 400 MPa, 20 min) sterilization and ultra‐high temperature (UHT, 126 ℃, 15 s) sterilization, respectively. The physicochemical properties, sensory characteristics, and the volatile components of watermelon juice during the 16‐week storage were investigated. The results showed that UHP treatment inactivated the microbial colonies (4.02 log CFU/ml) and kept the original color (△ E value was 1.1) and flavor of the watermelon juice. However, the overall flavor of UHT watermelon juice was out of harmony, the nonanal, 3, 7‐dimethyl‐2, 6‐octadienal, and geranyl acetone decreased by 74.4, 94.4, and 63.9%, respectively. Finally, based on the electronic tongue analysis of principal components, the discrimination index value of the UHP watermelon juice was less than 80, which meant that UHP treatment could keep the original flavor of watermelon juice during storage. Compared with UHT, UHP showed better commercial application prospects in watermelon juice. Practical applications: The effects of ultra‐high pressure (UHP) and ultra‐high temperature sterilization treatments on the quality of watermelon juice during 16‐week storage were compared in this research. It could provide a theoretical basis for the commercial production of UHP watermelon juice.